Thematic Progression in Children Stories - Linda, Linda (Universitas Swadaya Gunung Jati, 2013)
This paper is intended to analyze the Thematic Progression in Children Stories. The data are taken from three story book. They are Dinosaurus Loveable: Pterodactyl, The Journey of the Noble Gnarble, The Donkey and the Lion. The Objective of this research is to analyze how the types of thematic progression are found in the text of children. At the end of analyses the writer found that the texts for children are constructed by two or three types of Thematic Progression. Constant Theme Pattern and Simple Linear Pattern are two types of Thematic Progression that occur mainly in the Texts for Children.